Treatment and Prevention of Pandemic H1N1 Influenza - Suresh Rewar; Dashrath Mirdha; Prahlad Rewar (Ubiquity Press, 2016)
Background: Swine influenza is a respiratory infection common to pigs worldwide caused by type A influenza viruses, principally subtypes H1N1, H1N2, H2N1, H3N1, H3N2, and H2N3. Swine influenza viruses also can cause moderate to severe illness in humans and affect persons of all age groups. People in close contact with swine are at especially high risk. Until recently, epidemiological study of influenza was limited to resource-rich countries. The World Health Organization declared an H1N1 pandemic on June 11, 2009, after more than 70 countries reported 30,000 cases of H1N1 infection. In 2015, incidence of swine influenza increased substantially to reach a 5-year high. In India in 2015, 10,000 cases of swine influenza were reported with 774 deaths. Methods: The Centers for Disease Control and Prevention recommend real-time polymerase chain reaction as the method of choice for diagnosing H1N1. Antiviral drugs are the mainstay of clinical treatment of swine influenza and can make the illness milder and enable the patient to feel better faster. Findings: Antiviral drugs are most effective when they are started within the first 48 hours after the clinical signs begin, although they also may be used in severe or high-risk cases first seen after this time. The Centers for Disease Control and Prevention recommends use of oseltamivir (Tamiflu, Genentech) or zanamivir (Relenza, GlaxoSmithKline). Conclusion: Prevention of swine influenza has 3 components: prevention in swine, prevention of transmission to humans, and prevention of its spread among humans. Because of limited treatment options, high risk for secondary infection, and frequent need for intensive care of individuals with H1N1 pneumonia, environmental control, including vaccination of high-risk populations and public education are critical to control of swine influenza out breaks.